Local Taxation Awareness in Rural Communities in Poland - Patrycja SWIERCZEK-DUTKA (Communications of International Proceedings, 2021)
The aim of this paper is to determine the level of local taxation awareness among owners of properties located in rural communities in Poland. This aim was achieved through a pilot study using the following research methods: a questionnaire interview and a survey questionnaire. The study provided valuable information to support three hypotheses which will be verified at later stages of the project, namely: (1) there are marked differences in the level of taxation awareness of rural and urban communities; (2) local taxation awareness of entrepreneurs is more pronounced than that of private persons; (3) the declared understanding of local taxation mechanisms is not correspondent with the level of knowledge required for their correct settlement.
Keywords: Taxation Awareness; Local Taxation; Tax System; Rural Communities